Juridical Study of Premarital on Joint Property which Made by Notary and Legal Consequences in The District of Kudus - Pulung Jati Kusuma; Akhmad Khisni (Jurnal Akta, 2018)
Premarital agreements on joint property made before or during the marriage took place, the parties may determine the contents of the agreement, especially respect the innate property of each party in a premarital agreement. In Act No. 1 of 1974 About the Marriage of Article 29 paragraph (1) confirms that at the time or before the marriage took place two parties by mutual consent may submit a written agreement authorized by the employee registrar of marriage, after which it shall also apply to third parties lodged. Having made premarital agreement then the next must be registered in the district court clerk's office in legal marriages were held, the purpose of such registration in order to satisfy the principle of publicity. Background of the problem, authors conducted a study entitled "Juridical Study Of Premarital On Joint Property Which Made By Notary And Legal Consequences In The District Of Kudus". This study raises the issue of implementation of joint property on premarital agreement made by the notary in Kudus and the legal consequences of the implementation of a premarital agreement. The purpose of this study is to investigate the implementation of the agreement For Premarital of joint property made by a notary in Kudus and to know the legal consequences of a premarital agreement made by the notary. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analysis method. Based on the results of data analysis concluded that Premarital agreements about the estate property that is made before a notary in the Kudus District by husband and wife time before or after the course of the marriage as provided for in Article 29 of Act No. 1 of 1974 About Marriage asserts that the agreement must not violate limits of the law, religion and morality. Agreement it means the contents can be related to any of any one of them the separation of joint property during the agreement was detrimental to the parties and does not conflict with the nature and purpose of marriage. The legal consequences premarital agreement made by a notary it is binding and valid as the Law for the parties. If the premarital agreement that has been made by the husband and wife there was a violation.Keywords: Juridical Study; Premarital Agreements; Joint Property.